Observing the Reversible Single Molecule Electrochemistry of Alexa Fluor 647 Dyes by Total Internal Reflection Fluorescence Microscopy. (30th August 2019) - Fan, Sanjun; Webb, James E. A.; Yang, Ying; Nieves, Daniel J.; Gonçales, Vinicius R.; Tran, Jason; Hilzenrat, Geva; Kahram, Mohaddeseh; Tilley, Richard D.; Gaus, Katharina; Gooding, J. Justin
Abstract: Alexa Fluor 647 is a widely used fluorescent probe for cell bioimaging and super‐resolution microscopy. Herein, the reversible fluorescence switching of Alexa Fluor 647 conjugated to bovine serum albumin (BSA) and adsorbed onto indium tin oxide (ITO) electrodes under electrochemical potential control at the level of single protein molecules is reported. The modulation of the fluorescence as a function of potential was observed using total internal reflectance fluorescence (TIRF) microscopy. The fluorescence intensity of the Alexa Fluor 647 decreased, or reached background levels, at reducing potentials but returned to normal levels at oxidizing potentials. These electrochemically induced changes in fluorescence were sensitive to pH despite that BSA‐Alexa Fluor 647 fluorescence without applied potential is insensitive to pH between values of 4–10. The observed pH dependence indicated the involvement of electron and proton transfer in the fluorescence switching mechanism. Abstract : Alexa, schalt das Licht an : Ein System zur reversiblen potenzialgesteuerten Fluoreszenzschaltung von BSA‐Alexa Fluor 647 an ITO‐Elektroden wurde entwickelt. Es bietet sich als eine neue Sonde zur Untersuchung der Einzelmolekülelektrochemie an und demonstriert einen neuen Ansatz für Fluoreszenzschaltungen für die superhochauflösende Mikroskopie.